The Woman Painter in Victorian Literature - Losano, Antonia Jacqueline (Book collections on Project MUSE., 2008)
"The nineteenth century saw a marked rise both in the sheer numbers of women active in visual art professions and in the discursive concern for the woman artist in fiction, the periodical press, art history, and politics. The Woman Painter in Victorian Literature argues that Victorian women writers used the controversial figure of the woman painter to intervene in the discourse of aesthetics. These writers were able to assert their own status as artistic producers through the representation of female visual artists." "Women painters posed a threat to the traditional heterosexual erotic art scenarios - a male artist and a male viewer admiring a woman or feminized art object. Antonia Losano traces an actual movement in history in which women writers struggled to rewrite the relations of gender and art to make a space for female artistic production. She examines as well the disruption female artists caused in the socioeconomic sphere. Losano offers close readings of a wide array of Victorian writers, particularly those works classified as noncanonical - by Anne Thackeray Ritchie, Margaret Oliphant, Anne Bronte, and Mrs. Humphrey Ward - and a new look at better-known novels such as Jane Eyre and Daniel Deronda, focusing on the pivotal social and aesthetic meanings of female artistic production in these texts. Each of the novels considered here is viewed as a contained, coherent, and complex aesthetic treatise that coalesces around the figure of the female painter."--Jacket